2018
DOI: 10.1161/jaha.117.007529
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Baseline Serum Sodium in Heart Failure With Preserved Ejection Fraction

Abstract: BackgroundThe purpose of this study was to evaluate the relationship between serum sodium at the time of diagnosis and long term clinical outcomes in a large national cohort of patients with heart failure with preserved ejection fraction.Methods and ResultsWe studied 25 440 patients with heart failure with preserved ejection fraction treated at Veterans Affairs medical centers across the United States between 2002 and 2012. Serum sodium at the time of heart failure diagnosis was analyzed as a continuous variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
(45 reference statements)
3
35
0
2
Order By: Relevance
“…A meta-analysis of HF patients showed that low serum sodium values are associated with an increased risk of mortality [ 72 ]. We have previously shown in a national Veterans Affairs database study of 25,540 HFpEF patients that a J-shaped relationship is observed between serum sodium levels and a higher risk of number of days of HF hospitalizations and all-cause hospitalizations per year [ 73 ]. Such a relationship exists with baseline measurements of serum sodium levels at the time of diagnosis of HF as well as during longitudinal follow-up.…”
Section: Serum Sodium Values and Hfmentioning
confidence: 99%
“…A meta-analysis of HF patients showed that low serum sodium values are associated with an increased risk of mortality [ 72 ]. We have previously shown in a national Veterans Affairs database study of 25,540 HFpEF patients that a J-shaped relationship is observed between serum sodium levels and a higher risk of number of days of HF hospitalizations and all-cause hospitalizations per year [ 73 ]. Such a relationship exists with baseline measurements of serum sodium levels at the time of diagnosis of HF as well as during longitudinal follow-up.…”
Section: Serum Sodium Values and Hfmentioning
confidence: 99%
“…In cardiovascular diseases such as HF, electrolyte imbalances are frequently encountered and related to the excessive activation of the renin-angiotensin-aldosterone system as well as the use of specific medications (e.g. Among these, hypo-as well as hypernatremia has been related to higher risk of all-cause mortality in HFpEF patients (Patel et al, 2018). The most common electrolyte disturbances in HF patients are hyponatremia, hypokalemia and hypomagnesemia (Urso et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The most common electrolyte disturbances in HF patients are hyponatremia, hypokalemia and hypomagnesemia (Urso et al, 2015). Among these, hypo-as well as hypernatremia has been related to higher risk of all-cause mortality in HFpEF patients (Patel et al, 2018). Moreover, hypokalemia has been associated with greater risk of ventricular arrhythmia (Bielecka-Dabrowa et al, 2012;Pezhouman et al, 2015), a major cause of sudden death in HF patients (John et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…documentaron una prevalencia de 21% en pacientes con fracción de eyección conservada (27). También se documentó que algunos pacientes que ingresaban sin hiponatremia posteriormente la presentaban en alguna de las dos mediciones posteriores; sin embargo, no se puede establecer una prevalencia definitiva de la hiponatremia intrahospitalaria, dado que no se tuvieron datos de todos los pacientes y se realizaron a lo sumo tres mediciones durante la estancia hospitalaria, sin realizarse en todos los pacientes medición de sodio el día del egreso, lo cual es importante teniendo en cuenta la dinámica de las concentraciones de sodio en sangre durante el manejo de estos pacientes.…”
Section: Discussionunclassified